Transformação genética de soja usando biobalística, Agrobacterium e método integrado, em meio com ácido lipóico - Favreto, Cláudia Batista (2012)
Genetic engineering and biotechnology have, some of the barriers associated with plant breeding programs were eliminated, and it became possible to transfer genes between individuals of different species. This work was carried out to compare the efficiency of soybean transformation via biolistics, Agrobacterium and integrated system, and the addition of different concentrations of lipoic acid to the regeneration media. Concentrations used were 50, 100, 250 and 500 μM of lipoic acid, and a control group. Was used for processing the binary vector pCambia 3301 and evaluation of the efficiency of transformation was performed by histochemical assay with the GUS gene. The integrated method was more efficient processing, followed by Agrobacterium and biolistic system. There were obtained transgenic plants regenerated via biolistic transformation and integrated. For transformation via Agrobacterium efficiency of regeneration of transgenic plants was 0.4%. The plants obtained were chimeric, with tissues containing the transgene and non-transgenic tissues. The regeneration of plants subjected to transformation was higher in concentrations between 50 and 250 μM lipoic acid, the concentration of 100 μM had the greatest number of regenerated plants.